2017
DOI: 10.1037/met0000095
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of latent class, K-means, and K-median methods for clustering dichotomous data.

Abstract: The problem of partitioning a collection of objects based on their measurements on a set of dichotomous variables is a well-established problem in psychological research, with applications including clinical diagnosis, educational testing, cognitive categorization, and choice analysis. Latent class analysis and K-means clustering are popular methods for partitioning objects based on dichotomous measures in the psychological literature. The K-median clustering method has recently been touted as a potentially us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 112 publications
5
45
0
1
Order By: Relevance
“…We switched from a "variable-centered" to a "personcentered" approach to understanding the characteristics of ISS. Clustering methods are useful for grouping subjects into profiles that summarize shared aspects of a disease within a heterogeneous group (Brusco et al 2017). It has already been used in studies of respiratory diseases (Haldar et al 2008;Herr et al 2012;Dumas et al 2016), but has never been applied to children with ISS.…”
Section: Introductionmentioning
confidence: 99%
“…We switched from a "variable-centered" to a "personcentered" approach to understanding the characteristics of ISS. Clustering methods are useful for grouping subjects into profiles that summarize shared aspects of a disease within a heterogeneous group (Brusco et al 2017). It has already been used in studies of respiratory diseases (Haldar et al 2008;Herr et al 2012;Dumas et al 2016), but has never been applied to children with ISS.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are less effective, or even inapplicable, for certain types of data. For example, Brusco, Shireman, and Steinley () recently found that K ‐median clustering was better than K ‐means at recovering true cluster structure when objects are measured on binary variables. In light of the similarities (discussed in Section 2.3) between K ‐median clustering and affinity propagation, the latter method is also likely to perform well for such data.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods of the taxonomic approach are: 1) methods based on partitioning (partition-based, partitioning-based) or center (center-based) (for example, k-means [15], PAM (k-medoids) [16], FCM [17], ISODA-TA [18]);…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%